Pathogenicity and management of root-knot nematode (Meloidogyne incognita) in pointed gourd (Trichosanthes dioica) - MAHAPATRA, S N; SWAIN, P K; BEHERA, B (The Indian Journal of Agricultural Sciences, 2013)
Significant reduction in shoot and root weight of pointed gourd (Trichosanthes dioica Roxb.) was observed at aninitial inoculum density of 1 000 j 2 of Meloidogyne incognita per kg soil and hence was considered as the damagingthreshold level. The rate of nematode reproduction was density dependent, the maximum being at the lowest inoculumdensity and the minimum at the highest density. Bare-root dip of 10-day-old rooted seedlings of pointed gourd in0.05% concentration of carbosulfan 25 EC for 8 hr effectively reduced nematode multiplication and root galling. Rootdip in 0.1 % carbosulfan for 6 hr exhibited lethal toxicity in seedlings.